2016
DOI: 10.1098/rsbl.2016.0660
|View full text |Cite
|
Sign up to set email alerts
|

Androgens predict parasitism in female meerkats: a new perspective on a classic trade-off

Abstract: The immunocompetence handicap hypothesis posits that androgens in males can be a 'double-edged sword', actively promoting reproductive success, while also negatively impacting health. Because there can be both substantial androgen concentrations in females and significant androgenic variation among them, particularly in species portraying female social dominance over males or intense female -female competition, androgens might also play a role in mediating female health and fitness. We examined this hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Female meerkats have previously been shown to have increased androgen levels, linked to an immunocompromised state (Smyth et al . ). Alternatively, infected males may be more likely to be lost to follow‐up before they develop signs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Female meerkats have previously been shown to have increased androgen levels, linked to an immunocompromised state (Smyth et al . ). Alternatively, infected males may be more likely to be lost to follow‐up before they develop signs.…”
Section: Discussionmentioning
confidence: 97%
“…The outcome of interest in the present study was disease rather than infection, and the possibility exists that males could have higher infection rates than females, but with infected females progressing to clinical disease due to sex-linked immunosuppression. Female meerkats have previously been shown to have increased androgen levels, linked to an immunocompromised state (Smyth et al 2016). Alternatively, infected males may be more likely to be lost to follow-up before they develop signs.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that there is flexibility in a system that balances reproductive tradeoffs between classes (e.g. [113]) under varying environmental conditions. As revealed by the reduced differential in female reproductive success, it may be that certain environmental stressors, such as food shortage, are experienced comparably between the classes.…”
mentioning
confidence: 80%
“…There are other recent studies that have found support for testosterone playing an important role in parasite infections and fitness: in white-footed mice (Peromyscus leucopus), increased testosterone maintained social behaviours that increased the transmission potential of ectoparasites (Grear et al, 2009), and increasing testosterone in house mice (Mus musculus) increased their endoparasite intensity (Zhang and He, 2014). In red grouse (Lagopus lagopus), increased testosterone had a negative effect on body condition (Martínez-Padilla et al, 2014) and higher levels of testosterone were positively correlated to increasing ectoparasite intensity in female meerkats (Suricata suricatta) (Smyth et al, 2016). However, other studies have also failed to find a relationship between increased testosterone and immunocompetence measurements in mammals and birds (Nunn et al, 2009;van Oers et al, 2011;Roberts et al, 2007;Ros et al, 2006), and some studies have even found that elevated testosterone had immune-enhancing effects, completely opposite to predictions from the ICHH (Bilbo and Nelson, 2001;Evans et al, 2000).…”
Section: Discussionmentioning
confidence: 99%